Waduk Parangjoho dan Songputri: Alternatif Sumber Erupsi Formasi Semilir di daerah Eromoko, Kabupaten Wonogiri, Jawa Tengah - Bronto, Sutikno; Mulyaningsih, Sri; Hartono, G.; Astuti, B. (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no2.20091The Semilir Formation was typically originated from products of a very explosive volcanic activity, i.e. breccias, lapillistones, and tuffs containing abundant pumice. It has a light grey to white colour and high silica andesite to dacite in composition, mainly rich in volcanic glass and quartz. Sedimentary structures of these volcanic rocks are massive, grading, planar bedding, and cross-bedding to antidunes, with grain size varies from ash (≤ 2 mm) to lapilli (2 – 64 mm) to bomb and block (> 64 mm). The formation is widely distributed from the west side (Pleret and Piyungan areas, Bantul Regency, Special Province of Yogyakarta) until Eromoko area in the east (Wonogiri Regency, Jawa Tengah Province). Stratigraphically, the Semilir Formation underlies the Nglanggeran Formation, and overlies the Mandalika Formation in the eastern part and Kebo-Butak Formation in the western part. Geomorphological- and lithological analyses of the Semilir Formation in areas of Parangjoho and Song- putri Dams, Eromoko Sub-regency, Wonogiri Regency indicate that the two depressions were alternatively volcanic sources of the Semilir Formation in the Eromoko area. This is proved by the presence of co-ignimbrite breccias(co-ignimbrite lag fall deposits), that descriptively they are polymict breccias. This rock is characterized by a mixing of pumice and various hard rock fragments that primarily are juvenile materials (volcanic blocks, bombs), accessory-, and accidental rock fragments set in pumice-rich volcanic ash and lapilli sizes. The accessory materials came from older volcanic rocks, whereas the accidental ones were originated from basement rocks. During a caldera forming event or a destruction period of an older composite volcanic cone(s), all older rocks resting above the magma chamber were ejected to the surface by a very high magmatic pressure. Since they were heavier than the juvenile material, most accessory and accidental rock fragments were left (lag fall) in caldera rim behind the ash and pumice flow. In the dam areas of Parangjoho and Songputri, the lag fall fragments consisting of andesite, pyroxene andesite, dacite, and pumice, being 10 – 150 cm in diameter are set in pumice-rich lapilli tuffs. Some of the rock fragments are volcanic blocks and bombs, while the older rocks are angular to very angular shape, having prismatic jointing or jigsaw-crack structures. The eruptions in the Parangjoho and Songputri craters were controlled by north-south trending fractures, and they resemble to the Katmaian caldera explosion type.